Correction to: Low serum estradiol levels are related to Mycobacterium avium complex lung disease: a cross-sectional study - Yoshifumi Uwamino; Tomoyasu Nishimura; Yasunori Sato; Eiko Tamizu; Takanori Asakura; Shunsuke Uno; Masaaki Mori; Hiroshi Fujiwara; Makoto Ishii; Hiroshi Kawabe; Mitsuru Murata; Naoki Hasegawa (BMC Infectious Diseases, 2020)
After publication of the original article [1], we were notified that units of testosterone in main text and abstract and units of DHEA-S in Fig. 1 and Table 4 are incorrect.